The influence of cultural and religious factors on cross-national variations in the prevalence of chronic back and neck pain: an analysis of data from the global burden of disease 2019 study - Rajkumar, Ravi Philip (Frontiers in Pain Research, 2023)
Introduction Low back pain and neck pain are among the most commonly reported forms of chronic pain worldwide, and are associated with significant distress, disability and impairment in quality of life. Though these categories of pain can be analyzed and treated from a biomedical perspective, there is evidence that they are both related to psychological variables such as depression and anxiety. The experience of pain can be significantly influenced by cultural values. For example, cultural beliefs and attitudes can influence the meaning attached to the experience of pain, the responses of others to a sufferer's pain, and the likelihood of seeking medical care for particular symptoms. Likewise, religious beliefs and practices can influence the both experience of pain and the responses to it. These factors have also been associated with variations in the severity of depression and anxiety. Methods In the current study, data on the estimated national prevalence of both low back pain and neck pain, obtained from the 2019 Global Burden of Disease Study (GBD 2019), is analyzed in relation to cross-national variations in cultural values, as measured using Hofstede's model (n =115 countries) and in religious belief and practice, based on the most recent Pew Research Center survey (n = 105 countries). To address possible confounding factors, these analyses were adjusted for variables known to be associated with chronic low back or neck pain, namely smoking, alcohol use, obesity, anxiety, depression and insufficient physical activity. Results It was found that the cultural dimensions of Power Distance and Collectivism were inversely correlated with the prevalence of chronic low back pain, and Uncertainty Avoidance was inversely correlated with the prevalence of chronic neck pain, even after adjustment for potential confounders. Measures of religious affiliation and practice were negatively correlated with the prevalence of both conditions, but these associations were not significant after adjusting for cultural values and confounders. Discussion These results highlight the existence of meaningful cross-cultural variations in the occurrence of common forms of chronic musculoskeletal pain. Psychological and social factors that could account for these variations are reviewed, along with their implications for the holistic management of patients with these disorders.